An analysis of the competitive environment of Thai and Malaysian automotive industry - Tiamkare Thitithamtada; Johri, Lalit M.; Dimmitt, Nicholas J.; Sununta Siengthai; RTG Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2007)
This research aims to identify the external and internal factors of the automotive industry of Thailand and Malaysia in order to pinpoint the characteristics that contribute to the competitiveness as well as the weakness of their industry. In doing so, the analysis will be done by mean of a cross-national comparison of the strengths, weaknesses, opportunities and threats that lie in the industry of each country. Together with the expert opinions, as attained from interviews, the research will provide the insights and suggestions for the future automotive policies that will create competitiveness for the automotive industry in the ASEAN region. As the automotive industry of Thailand and Malaysia are moving towards becoming more liberalized. There are tradeoffs that need to be taken into consideration that is the negative effects that may occur on the local players in their countries. However, tradeoffs may be rather more critical in one country than the other as their national interests are different. Malaysia has its National Car projects whereas Thailand does not. It is interesting to see how the 2 countries are going to deisign their trade policies that will best cope with the situation they are facing.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration in International Business
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2007
Keywords: Automobile industry and trade -- Thailand; Automobile industry and trade -- Malaysia